Challenging the deficit discourse in medical schools through reverse mentoring—using discourse analysis to explore staff perceptions of under-represented medical students. Issue 12 (24th December 2021) - Curtis, Sally; Mozley, Heather; Langford, Chloe; Hartland, Joseph; Kelly, Jacquie
Abstract : Introduction: Despite the increasing diversity of UK medical students, students from low-socioeconomic backgrounds, some minority groups and members of communities with protected identities remain under-represented in medicine. In trying to ascertain why this under-representation persists, literature focuses on the barriers and challenges faced by under-represented students as opposed to the institution's responsibility to remove or mitigate these obstacles. One UK University created a reverse mentoring scheme enabling students to mentor senior members of the medical faculty to help them understand the perspectives and experiences of students from minority backgrounds. This paper explores whether changes in staff perceptions of under-represented students resulted from engaging with reverse mentoring. Methods: This qualitative study explored the impact of the reverse mentoring scheme. Staff mentees were required to write a narrative text about the Higher Education journey of an under-represented medical student before and after the reverse mentoring intervention. These texts were compared using discourse analysis to identify shifts in language use that demonstrated a change in perceptions. Results: The key themes from five senior staff members indicate a positive change in staff characterisation of the students and an acceptance of institutional responsibility for challenges faced. Initial texts revealed a superficial understanding of the student journey that focused on individual deficit but had fairy tale endings depicting the medical school as benevolent. The follow-up texts revealed a deeper understanding reflected by the portrayal of students as capable agents and containing pragmatic endings acknowledging the responsibility of the medical school. Conclusion: These findings highlight how removed senior staff can be from the reality of the student experience and that engaging with reverse mentoring helps to raise awareness and challenges the students face. This suggests a route for constructive change in medical schools and endorses the benefits of facilitating open discussion around educational inequity.